Human rights: the dark side of the fight against organised crime - Prieto-del-Pino, Ana María (My University, 2019)
An in-depth analysis of judicial decisions on money laundering and confiscation of proceeds of crime issued by European national courts and by the European Court of Human Rights in the last decade has been carried out from a human rights, legal guarantees and criminal law basic principles’ perspective. The undertaken study has revealed the violation of the right to property, of the proportionality principle and the infringement of basic principles of substantive and procedural criminal law systems. The most relevant ones have to do with the punishment of money laundering committed through negligence, non-conviction based confiscation and a too-far reaching interpretation of the notion of ‘proceeds of crime’.
Keywords: Derechos humanos; Crimen organizado; proceeds of crime; seizure and confiscation